Spectroscopic Study of Some 1,3,4-0xadiazole, 1,3,4- Thiadiazole and 1,2,4- Triazole Derivatives - Ibrahim, F.J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Compounds [II - [51 namely 2,5-(N,N’-diphenyldiamino) -1,3,4- oxadiazole [I], 2,5-(N,N’- diphenyl diamino) -1.3,4- thiadia:zole (2] ,4- phenyl Â·3-(N-phenyl amino)-5-hydroxy-1,2,4- triazolc [31 ,3,5-(N,N’Â diphenyl diamino)-1 ,2,4- triazolc r4) and 4-phenyl -5-(N-phenyl arnino)- 3- th io l -1 ,2.4Â· triazole [5) are prepared and studied. Their electronic spectra in different pH media and in dilferent solvents were studied. The lR spectrum of compounds [3) and [5] showed that these compounds are present in keto and thion tautomer, respectively. Electronic studies of compounds [3) and [51 in different pH media and solvents are reported and showed that these compounds arc not affected by the polarity of the solvent and the compounds [3] and [5] are affected by some pH media.